Bioinformatics for life sciences & drug design workshop 2023 / Dr. Siti Azma Yusof, Zakiah Mohd Noordin and Dr. Gurmeet Kaur Surindar Singh - Yusof, Siti Azma; Mohd Noordin, Zakiah; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
On 13-17th March, Faculty of Pharmacy UiTM organised a workshop on Bioinformatics for Life Sciences and Drug Design. Bioinformatics is a trans-disciplinary field involving computer technology (software, hardware, programming languages), physics, chemistry, and biology. Bioinformatics has been used in the discovery of new drugs, understanding genetic mutations, cancer, and various diseases. With the increasing availability of biological information in online databases, the skills to use these databases and bioinformatics tools become increasingly critical for those who want to pursue research in related fields.